PENGARUH CORPORATE GOVERNANCE PERCEPTION INDEX DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING - Ramadhani, Suci (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2015)
The aim of this study examines the effect of corporate governance perception index,debt policy on firm value by dividen policy as an the intervening variable. The studyis based sample of companies included in the ranking Corporate GovernancePreception Index (CGPI) by Indonesian Institute for Corporate Governance (IICG)years 2010-2012. The analysis method used in this study is multiple linearregressions expanded with path analysis using the SPSS 19. The result of thisresearch show that: 1) corporate governance perception index has not significantinfluence to dividend policy, 2) debt policy has not significant influence to dividendpolicy, 3) Corporate governance perception index has not significant influences tofirm value, 4) Debt policy has significant to firm value,. 5) dividend policy hassignificant to firm value, 6) dividend policy has not mediate corporate governanceperception and firm value, and 7) dividend policy has not mediate debt policy andfirm value.Keyword: corporate governance perception index, debt policy, dividend policy, andfirm value.